Specific Interventions for Implementing a Patient-Centered Approach to TB Care in Low-Incidence Cities - Pujol-Cruells, Adrià; Vilaplana, Cristina (Frontiers in Medicine, 2019)
Background: According to the latest Guidelines from the World Health Organization, there is an increasing need for patient-centered tuberculosis disease management given the socio-economic factors influencing the tuberculosis epidemic. In the present study, we aimed to study TB in Barcelona city from an anthropological point of view and to devise a series of specific proposals to implement a patient-centred approach in our setting. Methods: We carried out a qualitative study using an anthropological approach in Barcelona in the period between November 2017 and November 2018 and proposed specific interventions based on our observations. Results: In practice, in our environment (a low-incidence European country where tuberculosis tends to present in patients with multiple social problems), and despite the goodwill of the care teams, there are no established and stable circuits or specific tools to ensure that this is done routinely. Based on our observations, we have devised a series of specific proposals to implement a patient-centred approach. With these interventions we aim to a) directly ameliorate TB patients well-being in any diagnostic/healthcare management centre and b) at more general level, to increase TB detection and treatment adherence. Conclusions: The patient-centred TB management recommended by the WHO might be essential for patients’ wellbeing, but there is a lack of circuits or working protocols that ensure its implementation in a regulated manner. In the present manuscript we explain the various concrete measures that we propose in our region and which could be put into practice in other cities or geographic regions with similar epidemiological characteristics.